2005
DOI: 10.1152/ajprenal.00438.2004
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 binding modulates detachment of Na-K-ATPase following energy deprivation in renal epithelial cells

Abstract: The molecular mechanisms associated with reestablishment of renal epithelial polarity after injury remain incompletely delineated. Stress proteins may act as molecular chaperones, potentially modulating injury or enhancing recovery. We tested whether overexpression of heat shock protein 70 (HSP70) would stabilize Na-K-ATPase attachment to the cytoskeleton, under conditions of ATP depletion, and whether a direct association existed between Na-K-ATPase and HSP70 in cultured renal epithelial cells. LLC-PK1 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…In vitro studies also revealed that the overexpression of HSP72 is associated with decreased detachment of NKA from the cytoskeleton following ischemic injury (17). Based on our and others' previous results, here we hypothesized that the different expression and localization of HSP72 might also be responsible for gender disparity in NKA localization after the ischemic insult.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In vitro studies also revealed that the overexpression of HSP72 is associated with decreased detachment of NKA from the cytoskeleton following ischemic injury (17). Based on our and others' previous results, here we hypothesized that the different expression and localization of HSP72 might also be responsible for gender disparity in NKA localization after the ischemic insult.…”
Section: Discussionsupporting
confidence: 54%
“…Ischemic preconditioning with HSP72 overexpression prevented NKA ␣ 1 -subunit dissociation after repeated ischemic insult (1). Very recently, a direct interaction has been approved between HSP72 and damaged or displaced NKA ␣ 1 in an in vitro model of renal ischemic injury (17). Although these studies further support the concept that HSP72 and NKA have important interactions, no one has as yet investigated the gender differences in colocalization of these proteins after renal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…J proteins bind Hsp70 through the J domain and stimulate Hsp70's ATP hydrolysis activity as well as other activities such as de novo folding of client proteins, intervening when proteins are improperly folded-often during stress conditions, protein degradation, and the disassembly of complexes, protein translocation, and trafficking (8)(9)(10). A conserved HPD loop of J domains is essential for interaction with Hsp70 and modulating Hsp70 activities (8).…”
mentioning
confidence: 99%
“…HSP70 directly interacts with the Na + /K + -ATPase and stabilizes its cytoskeletal anchorage in renal outer medulla (Ruete et al, 2008) and epithelial cells (Riordan et al, 2005) after ATP depletion. Whether this interaction may represent a fundamental mechanism underlying cellular protection is unknown, but warrants investigating if stabilization of Na + /K + -ATPase by HSP70 contributes to restoring NCV in diabetic nerves.…”
Section: Namentioning
confidence: 99%